ANALYZING EARTHQUAKE ACTIVITY LEVELS IN NORTH SULAWESI USING MAXIMUM LIKELIHOOD METHOD AND GUTENBERG – RICHTER LAW - Wattimanela, Henry Junus (PATTIMURA UNIVERSITY, 2023)
Tectonic earthquakes are disasters that often cause damage to buildings and loss of life. The Province of North Sulawesi and its surroundings are earthquake-prone areas because they are located at the confluence of the major plates. This study aims to analyze the level of earthquake activity in the Province of North Sulawesi and its surroundings using the maximum likelihood method and the Guttenberg-Richter law. The distribution of the earthquake studied for the period 1941-2021 in the Province of North Sulawesi and its surroundings with a Mag ≥3.0 Mw and a depth ≤60 km. The data used comes from the Meteorological, Climatological, and Geophysical Agency Indonesia and ISC (International Seismological Center). The level of earthquake activity was reviewed based on nine groups of year intervals, three groups of depth levels, and the overall research area. The results show that the level of earthquake activity, rock fragility, and local stress at certain year intervals is sometimes high or low for the 1941-2021 earthquake period in North Sulawesi and its surroundings. The same condition for certain earthquake depths. On the other hand, the level of earthquake activity is quite high and the level of rock fragility is moderate in the research area as a whole.